2021
DOI: 10.3389/fcvm.2021.761112
|View full text |Cite
|
Sign up to set email alerts
|

External Counterpulsation Improves Angiogenesis by Preserving Vascular Endothelial Growth Factor-A and Vascular Endothelial Growth Factor Receptor-2 but Not Regulating MicroRNA-92a Expression in Patients With Refractory Angina

Abstract: Objective: External counterpulsation (ECP) provides long-term benefits of improved anginal frequency and exercise tolerance in patients with refractory angina (RA). This is postulated as a result of improved angiogenesis and endothelial function through an increase in shear stress. Angiogenesis is mainly represented by vascular endothelial growth factor-A (VEGF-A) and its receptor, vascular endothelial growth factor receptor-2 (VEGFR-2). The microRNA-92a (miR-92a) is a flow-sensitive miRNA that regulates ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In this study, the secretion of NO and the phosphorylation level of eNOS in HUVECs were measured, which signified that DGS significantly upregulated p-eNOS and stimulated the secretion of NO. Moreover, NO is one of the main mechanisms that promote angiogenesis [45]. Our results suggest that DGS can stimulate the secretion of VEGFA to upregulate VEGFR2, thereby accentuating the binding of VEGFA to VEGFR2.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, the secretion of NO and the phosphorylation level of eNOS in HUVECs were measured, which signified that DGS significantly upregulated p-eNOS and stimulated the secretion of NO. Moreover, NO is one of the main mechanisms that promote angiogenesis [45]. Our results suggest that DGS can stimulate the secretion of VEGFA to upregulate VEGFR2, thereby accentuating the binding of VEGFA to VEGFR2.…”
Section: Discussionmentioning
confidence: 61%
“…Brachial artery flow-mediated dilation and peak flow velocity were significantly enhanced after EECP treatment, and EECP alleviated vascular endothelial dysfunction in patients with angina pectoris [25–26] . Liu et al [27] observed changes in serum endothelin-1 (ET-1) and nitric oxide (NO) after EECP intervention by establishing a canine model of “automatic circulation recovery from cardiac arrest.” The results showed that the serum ET-1 concentration decreased and the serum NO concentration increased after EECP treatment, while the ET-1/NO ratio decreased.…”
Section: The Moa Of Eecpmentioning
confidence: 99%